Developing a "toolkit" to measure implementation of concurrent palliative care in rural community cancer centers. Issue 1 (1st June 2017) - Zubkoff, Lisa; Dionne-Odom, J. Nicholas; Pisu, Maria; Babu, Dilip; Akyar, Imatullah; Smith, Tasha; Mancarella, Gisella A.; Gansauer, Lucy; Sullivan, Margaret Murray; Swetz, Keith M.; Azuero, Andres; Bakitas, Marie A.
ABSTRACT: Objective: Despite national guidelines recommending early concurrent palliative care for individuals newly diagnosed with metastatic cancer, few community cancer centers, especially those in underserved rural areas do so. We are implementing an early concurrent palliative care model, ENABLE (E ducate, N urture, A dvise, B eforeL ifeE nds) in four, rural-serving community cancer centers. Our objective was to develop a "toolkit" to assist community cancer centers that wish to integrate early palliative care for patients with newly diagnosed advanced cancer and their family caregivers. Method: Guided by the RE-AIM (R each, E ffectiveness–A doption, I mplementation, M aintenance) framework, we undertook an instrument-development process based on the literature, expert and site stakeholder review and feedback, and pilot testing during site visits. Results: We developed four instruments to measure ENABLE implementation: (1) the ENABLE RE-AIM Self-Assessment Tool to assess reach, adoption, implementation, and maintenance; (2) the ENABLE General Organizational Index to assess institutional implementation; (3) an Implementation Costs Tool; and (4) an Oncology Clinicians' Perceptions of Early Concurrent Oncology Palliative Care survey. Significance of results: We developed four measures to determine early palliative care implementation. These measures have been pilot-tested, and will be integrated into a comprehensive "toolkit" to assist community cancer centers to measure implementation outcomes. We describe the lessons learned and recommend strategies for promoting long-term program sustainability.